Radiography, computed tomography and magnetic resonance imaging at 0.5 Tesla of mechanically inducedosteoarthritis in rabbit knees - Torelli, S. R. [UNESP]; Rahal, Sheila Canevese [UNESP]; Volpi, R. S. [UNESP]; Yamashita, S. [UNESP]; Mamprim, Maria Jaqueline [UNESP]; Crocci, A. J. [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 2004)
In the present experimental study we assessed induced osteoarthritis data in rabbits, compared three diagnostic methods, i.e., radiography (XR), computed tomography (CT) and magnetic resonance imaging (MRI), and correlated the imaging findings with those obtained by macroscopic evaluation. Ten young female rabbits of the Norfolk breed were used. Seven rabbits had the right knee immobilized in extension for a period of 12 weeks (immobilized group), and three others did not have a limb immobilized and were maintained under the same conditions (control group). Alterations observed by XR, CT and MRI after the period of immobilization were osteophytes, osteochondral lesions, increase and decrease of joint space, all of them present both in the immobilized and non-immobilized contralateral limbs. However, a significantly higher score was obtained for the immobilized limbs (XT: P = 0.016, CT: P = 0.031, MRI: P = 0.0156). All imaging methods were able to detect osteoarthritis changes after the 12 weeks of immobilization. Macroscopic evaluation identified increased thickening of joint capsule, proliferative and connective tissue in the femoropatellar joint, and irregularities of articular cartilage, especially in immobilized knees. The differences among XR, CT and MRI were not statistically significant for the immobilized knees. However, MRI using a 0.5 Tesla scanner was statistically different from CT and XR for the non-immobilized contralateral knees. We conclude that the three methods detected osteoarthritis lesions in rabbit knees, but MRI was less sensitive than XR and CT in detecting lesions compatible with initial osteoarthritis. Since none of the techniques revealed all the lesions, it is important to use all methods to establish an accurate diagnosis.
Keywords: Osteoarthritis; Rabbit knee osteoarthritis; Imaging diagnosis; Knee immobilization; Radiography; Computed tomography; Magnetic resonance imaging